Determination of Catastrophic Health Expenditures among Elderly People in Iran - Sara Emamgholipour; Vahid Saberzadeh; Hossein Dargahi (Tehran University of Medical Sciences, 2020)
Background and Aim: Given the rising trend of ageing and the vulnerability of the aged group to diseases and health costs, it is important to determine the exposure of elderly households to the burdensome costs of health. Materials and Methods: The incidence and severity of elderly costs at provincial level and income quintiles were calculated; besides, chi-square test was used to determine the relationship between household socioeconomic variables and exposure levels. The sample included 9103 elderly people aged 65 and over, and the data of their own and their households were extracted from the statistical center in 2016. Data analysis was performed using SPSS16 software. Results: The exposure rate of households with rural elderly people (9.74%) was higher than urban ones (6.2%), and the intensity of exposure was higher in rural areas than urban. In both groups, the highest exposure was in the second and the lowest in the fifth quintiles. The elderly households in Hormozgan province had the highest and in Kohgiluyeh and Boyer-Ahmad had the lowest exposure. Number of elderly people in family, place of residence, employment status, household dimension, costs of chemotherapy, addiction abandonment, orthopedics, special medications, household spending and out-of-pocket payment for health services were significantly correlated with exposure. However, elderly personchr('39')s literacy, insurance, marital status and the presence of persons under 12 years in the family did not show a significant relationship with the amount of exposure. Conclusion: The exposure rate and its intensity is higher among rural elderly people than urban ones, and the exposure of poorer elderly people is higher; these points indicate that the distribution of financial resources in the health system is not fair and requires  purposeful policymaking decisions for these groups.